STRATEGI PEMASARAN TABUNGAN TAPLUS MUDA DALAM UPAYA MENINGKATKAN JUMLAH NASABAH PT. BANK NEGARA INDONESIA (Persero), Tbk. CABANG PONDOK PINANG - Tannia Regina (ITB Swadharma, 2020)
Business competition in the banking industry is getting sharper. Each bank is competing to create and introduce products and services with the marketing system that is owned. A bank must be able to guarantee the survival of the bank, and a bank must be able to compete with the main objective to satisfy the needs of society. Because people have more diverse needs, they will be more selective choose a bank that is able to provide the best service quality. This is an impact of the increasing demands of customers to obtain maximum satisfaction. For that marketing efforts will be bank products are not easy, meaning that a bank is constantly reviewing the marketing strategy that has been determined by the current conditions. The banking sector must be aware of the importance of marketing a product, because marketing is a tool for introducing bank products that we offer to potential customers. So the better the effort marketing, will also increase the development of these product customers. In terms of the customer itself with developments information and technology makes customers smarter, and more thorough in finding good services at relatively competitive prices